2012
DOI: 10.1080/09512748.2012.685098
|View full text |Cite
|
Sign up to set email alerts
|

Resource security: a new motivation for free trade agreements in the Asia-Pacific region

Abstract: ABSTRACT:Following a historical commitment to multilateralism, in the last decade the trade policy initiatives of many states in the Asia-Pacific have turned to bilateralism through the negotiation of free trade agreements (FTAs). The corresponding proliferation of regional FTAs has thus far been understood to result from three broad motivations: a desire to advance trade liberalisation beyond WTO disciplines; mercantilistic efforts to secure preferential access to key export markets; and/or attempts to use FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Agreements involving China and ASEAN members also rarely address any of the WTO Plus issues -such as investment, intellectual property and technical barriers to trade -in a substantive way that improves upon or extends existing WTO rules (Capling and Ravenhill 2011). As a result, many analysts have argued that FTAs in the Asia-Pacific have failed to live up to their promise of advancing either trade liberalisation, or broader forms of regional economic cooperation, in a meaningful way (Capling 2008a;Dent 2010;Ravenhill 2008;Wilson 2012).…”
Section: The Rise Of Free Trade Agreements In the Asia-pacificmentioning
confidence: 92%
See 1 more Smart Citation
“…Agreements involving China and ASEAN members also rarely address any of the WTO Plus issues -such as investment, intellectual property and technical barriers to trade -in a substantive way that improves upon or extends existing WTO rules (Capling and Ravenhill 2011). As a result, many analysts have argued that FTAs in the Asia-Pacific have failed to live up to their promise of advancing either trade liberalisation, or broader forms of regional economic cooperation, in a meaningful way (Capling 2008a;Dent 2010;Ravenhill 2008;Wilson 2012).…”
Section: The Rise Of Free Trade Agreements In the Asia-pacificmentioning
confidence: 92%
“…Third, others have been forced to defensively begin signing FTAs in order to neutralise disadvantages associated with being "outsiders" to the web of agreements gradually spreading across the region (Dent 2010). Finally, some regional governments have used FTAs for geopolitical rather than purely economic purposes: to "reward" security partners (Higgott 2004), to signal diplomatic intentions (Capling 2008b), and to pursue non-trade forms of economic cooperation (such as resource security agreements) (Wilson 2012). The consequence of FTA proliferation is that the trade system in the AsiaPacific is no longer flat and multilateral, but dominated by a complex web of overlapping bilateral agreements with markedly different designs and purposes.…”
Section: The Rise Of Free Trade Agreements In the Asia-pacificmentioning
confidence: 96%
“…FTAs are sometimes concluded to enhance the state's security position in evolving global and regional politics (Aggarwal and Govella 2013;Pempel 2013). The resource-importing countries take advantage of FTAs to improve "resource security" in which they can enjoy the continuous availability of necessary natural resources at reasonable prices (Wilson 2012). Second, political conditions have crucial influences on the selection of FTA partners.…”
Section: Diplomatic Objectives In Pursuing Fta Policiesmentioning
confidence: 99%
“…In contrast to the marked changes in interstate relations brought about by BITs, government attempts to increase resource security through investment-related provisions in PTAs have enjoyed minimal success. A survey of minerals chapters in PTAs involving East Asian countries (Wilson 2012) found that all of the ten agreements with resource suppliers that included investment protection provisions had significant exemptions for resource sectors. Moreover, none of the resource chapters included a commitment on the part of exporting states to refrain from imposing export controls (the only agreements that mentioned export controls, those between Japan and Indonesia and Japan and Brunei, merely require consultation on quantitative restrictions and, in both instances, the suppliers reserve the right to impose such restrictions if they see fit -a much weaker discipline than found, for instance, in the EU's trade agreements with Algeria and South Africa (WTO 2010: 180)).…”
Section: Bilateral Arrangementsmentioning
confidence: 99%